2014
DOI: 10.1371/journal.pone.0104037
|View full text |Cite
|
Sign up to set email alerts
|

Field Metabolic Rate and PCB Adipose Tissue Deposition Efficiency in East Greenland Polar Bears Derived from Contaminant Monitoring Data

Abstract: Climate change will increasingly affect the natural habitat and diet of polar bears (Ursus maritimus). Understanding the energetic needs of polar bears is therefore important. We developed a theoretical method for estimating polar bear food consumption based on using the highly recalcitrant polychlorinated biphenyl (PCB) congener, 2,2′,4,4′,55-hexaCB (CB153) in bear adipose tissue as an indicator of food intake. By comparing the CB153 tissue concentrations in wild polar bears with estimates from a purposely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…However, the consequences of global changes have not been considered in the present study, and the main assumption is that polar bear feed only on ringed seal. A similar diet simplification was assumed recently by Pavlova et al in their modeling exercise.…”
Section: Methodsmentioning
confidence: 80%
“…However, the consequences of global changes have not been considered in the present study, and the main assumption is that polar bear feed only on ringed seal. A similar diet simplification was assumed recently by Pavlova et al in their modeling exercise.…”
Section: Methodsmentioning
confidence: 80%
“…These scenarios indicate that the East Greenland population of polar bears may be more endangered than anticipated. A recent simulation of the field metabolic rate indicated that even relatively small reductions in feeding opportunities could affect the survival of the polar bears in East Greenland (Pavlova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Models in marine mammal toxicology follow the same principles, but face probably more challenges as the biology and physiology of most marine mammal species is often scarcely known and biomonitoring data is usually focussed on just a few tissues. Nevertheless, several types of marine mammal models are available for cetaceans and pinnipeds (reviewed in Weijs et al 2014) and polar bears (Sonne et al 2009;Pavlova et al 2014).…”
Section: In Silico Researchmentioning
confidence: 99%